A comparative study on the properties of c-plane and a-plane GaN epitaxial films grown on sapphire substrates by pulsed laser deposition. (June 2016) - Wang, Wenliang; Yang, Weijia; Wang, Haiyan; Zhu, Yunnong; Yang, Meijuan; Gao, Junning; Li, Guoqiang
Abstract: ∼500 nm-thick c -plane and a -plane GaN epitaxial films on c -plane and r -plane sapphire substrates by pulsed laser deposition have been grown and explored. The ∼500 nm-thick c -plane GaN epitaxial films grown on c -plane sapphire substrates show high crystalline quality with full-width at half-maximum (FWHM) for GaN(0002) and GaN(10–12) X-ray rocking curves (XRCs) of 0.20° and 0.37°, respectively, very smooth GaN surface with a root-mean-square (RMS) surface roughness of 1.4 nm, sharp and abrupt c -plane GaN/ c -plane sapphire hetero-interfaces, a −0.116 GPa residual stress, and high optical property. These results are in striking contrast to those of ∼500 nm-thick a -plane GaN epitaxial films grown on r -plane sapphire substrates. The ∼500 nm-thick a -plane GaN epitaxial films grown on r -plane sapphire substrates show poor crystalline quality with FWHM for GaN(11–20) and GaN(10–11) XRC of 0.72° and 0.81°, respectively, rough GaN surface with an RMS surface roughness of 7.2 nm, indistinct a -plane GaN/ r -plane sapphire hetero-interface with a ∼1.5 nm-thick interfacial layer, a −0.884 GPa residual stress, and poor optical property. This work brings further insight into fully understanding of the properties of GaN epitaxial films grown on c -plane and r -plane sapphire substrates for obtaining high-quality GaN epitaxial films in the application of GaN-based devices. Highlights: The c -plane and a -plane GaN epitaxial films have been grown on sapphire substrates by pulsed laser deposition. The properties of c -plane and a -plane GaN epitaxial films are studied comparatively. The further insight of c -plane and a -plane GaN epitaxial films grown on sapphire substrates is well analyzed.